PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DAKOTA CARGO DENPASAR - I Komang Deky Astawa; Wayan Mendra; Tjok Istri Sri Harwathy (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Performance is the result of work that can be achieved by a person or group of people in an organization, in accordance with their respective responsibilities and authorities in an effort to achieve organizational goals. Factors that can affect employee performance are work motivation and work discipline. The purpose of this study was to determine the effect of motivation and work discipline on employee performance at PT Dakota Cargo Denpasar. The location of this research was conducted at PT. Dakota Cargo Denpasar which is located on Jl. Cargo game no.139 kel. Ubung kaja, Denpasar, with the object of research at PT. Dakota Cargo Denpasar is Motivation, Work Discipline and Employee Performance. The population in this study is a group of people, namely all employees of PT. Dakota Cargo Denpasar, which amounted to 37 people, with the number of samples using the entire existing population will be used as research respondents, as many as 37 people. The data analysis technique used is multiple linear regression analysis. The results showed that motivation had a positive and significant effect on employee performance at PT. Dakota Cargo Denpasar. This means that the better the motivation given to employees will improve performance. Work discipline has a positive and significant effect on employee performance at PT. Dakota Cargo Denpasar. This means that the better the work discipline you have, the more employees you will have.